Six capitals : capitalism, climate change and the accounting revolution that can save the planet - Gleeson-White, Jane (Allen & Unwin, 2020)
Six Capitals is the story of a 21st-century revolution led by the most unlikely of rebels: accountants ... It is only the third revolution in accounting since double-entry bookkeeping emerged in medieval Italy - and it's proceeding apace, driven by the 2008 financial crash and the environmental crisis. The changes it will wreak are profound and far-reaching ... The accounts of nations and corporations are key to the 21st century global economy. They translate value into the language of modern times, numbers and money, in the shape of GDP and profit figures. They rule the world. And so this accounting revolution is set to redefine our values for the 21st century, force us to rethink capitalism - as 'sustainable capitalism' - and affect the future of the planet ... In May 2012 these changes seemed plausible but unlikely to take place. Today they are unfolding at speed. 2012 was the sea-change year. Two key initiatives took root that year: an international movement to transform corporate accounting for the 21st century, aka the International Integrated Reporting Council (IIRC), led by Professor Mervyn King, former lawyer to Nelson Mandela and Shane Warne. The other is the rise of natural capital accounting for nations and the global economy, endorsed by the United Nations in 2012, driven by the World Bank and to date most comprehensively practised by the UK ... This accounting revolution entails accounting for nature and rethinking the idea of 'capital' to include four new categories along with the former two, financial and industrial capital. The new capitals are intellectual, human, social and relationship, and natural capital. Accounting for them is controversial and difficult to achieve, but many believe it is the only way to address the many crises of the new millennium. Six Capitals tells the story of their rise to prominence - and their promise and threat.